2006
DOI: 10.1039/b509939k
|View full text |Cite
|
Sign up to set email alerts
|

Shear force induced monodisperse droplet formation in a microfluidic device by controlling wetting properties

Abstract: Perpendicular flow is used to induce oil droplet breakup by using a capillary as water phase flow channel. It is a new route to produce monodisperse emulsions. The wetting properties of the fluids on the walls are exceedingly important parameters. Depending on the oil and water flow rates, different spatial distributions of the two phases as laminar, plugs, cobbles and drops, are obtained. The effects of two-phase flow rates on plugs and drop size are studied, and the different droplet formation mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
162
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 25 publications
13
162
0
Order By: Relevance
“…The wetting properties of microchannel walls can be altered by surface modification (Shui et al, 2009) or changing the concentration of surfactants in liquid streams (Xu et al, 2006b). It has been found that both O/W and W/O emulsions can be prepared in the same T junction device, solely by an appropriate choice of surfactants added to the oil or water phase (Xu et al, 2006c).…”
Section: T Junctionmentioning
confidence: 99%
“…The wetting properties of microchannel walls can be altered by surface modification (Shui et al, 2009) or changing the concentration of surfactants in liquid streams (Xu et al, 2006b). It has been found that both O/W and W/O emulsions can be prepared in the same T junction device, solely by an appropriate choice of surfactants added to the oil or water phase (Xu et al, 2006c).…”
Section: T Junctionmentioning
confidence: 99%
“…Due to these facts, recently, attention has been given to immiscible liquid-liquid microfluidic systems with a focus on intensification of mass transfer and reaction by dispersing one phase into the other as droplets. Numerous studies concerning the flow patterns of liquid-liquid systems in microchannels have indicated that the flow pattern can be controlled by the channel geometry, interfacial properties of fluids and channel surface, as well as the flow rate of two immiscible liquids [11][12][13] . The flow pattern and droplets formation mechanism of dispersed phase have been experimentally studied by several authors, who have discussed the flow regimes in microchannels viz.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous phase (usually oil) breaks the flow of the dispersed phase (usually water) to create droplets at the junction of the two channels. The force applied by oil at the point of creation is known as shear force 33 . The size of the droplets can be controlled by controlling the flow rates of the two liquids.…”
Section: T Channelmentioning
confidence: 99%